PREPARATION AND CHARACTERIZATION OF STAVUDINE ENTRAPPED LIPOSPHERES - Ranjita Shegokar; Kamalinder Singh (Indonesian Journal of Pharmacy, 2012)
Lipospheres  of  stavudine  were  prepared  by  melt  dispersion technique  using  trimyristin,  tripalmitin and  triastearin,  stearic acid, Compritol®  888  ATO  and  Precirol®  ATO  5  as  lipid  matrix  in  the various  drug-lipid  ratios.  Drug  entrapped  free  flowing  solid lipospheres  of  triglycerides  and  glyceryl  behenate  were characterized  for  surface  morphology,  particle  size  distribution, encapsulation efficiency, and in vitrorelease behavior. The effect of drug lipid ratio, the surfactant used, concentration of stabilizer, and stirring  speed  were  identified  as  the  key  variables  affecting  the formation  of  discrete  spherical  lipospheres  and  sustained  drug release  rate.  The  lipospheres  production  conditions  were  optimized by using 2% w/w sodium cholate and 1% Plural oleic as a stabilizer. The  concentration  of  lipid  used  had  pronounced  effect  on  particle size of the lipospheres. The incorporation efficiency was found to be in range of 30  to  50%. Increase  in concentration of surfactant and stirring  speed  produced  fine  spherical,  smooth,  and  round lipospheres.  All  the  prepared  lipospheres  exhibited  slow  release profiles dictating the Higuchi mode of release.Key  words: Lipospheres,  stavudine,  lipid  matrix,  hydrophilic  surfactant, drug release